Data and Knowledge Engineering Third International Conference, ICDKE 2012, Wuyishan, China, November 21-23, 2012, Proceedings - Xiang, Yang; Pathan, Mukaddim; Tao, Xiaohui; Wang, Hua (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the refereed proceedings of the International Conference on Data and Knowledge Engineering, ICDKE 2012, held in Wuyishan, Fujian, China, in November 2012. The conference was co-located with the 6th International Conference on Network and System Security, NSS 2012. The 13 revised full papers of ICDKE 2012 were carefully reviewed and selected from 53 submissions. The papers cover the following topics: artificial intelligence and data engineering; knowledge discovery and data management; information extraction and retrieval and data security.